A branched cellulose-reinforced composite polymer electrolyte with upgraded ionic conductivity for anode stabilized solid-state Li metal batteries. Issue 10 (30th July 2019) - Wu, Hailong; Wang, Jiali; Zhao, Yu; Zhang, Xiaoqiang; Xu, Ling; Liu, Hao; Cui, Yixiu; Cui, Yanhua; Li, Chilin
Abstract : Branched cellulose filler is used to reinforce the PEO based polymer electrolyte, resulting in the upgraded ionic conductivity and anode stability for solid-state Li metal batteries. Abstract : Easy processing and flexibility make polymer electrolytes very promising in the field of all-solid-state Li metal batteries. However, their low room-temperature conductivity and poor mechanical properties hinder their application. Herein, methyl 2-hydroxyethyl cellulose (HEMC), an organic filler, was used to reinforce the PEO-based polymer electrolyte instead of traditional inorganic or ceramic fillers. PEO–LiTFSI–HEMC with a 20 wt% HEMC filling enables the highest ion conductivities of 1.30 × 10 −4 S cm −1 at 30 °C and 1.68 × 10 −3 S cm −1 at 60 °C with an increased Li-ion transference number (0.467), by providing multi-dimensional Li-ion transport channels at the cross-linking network interface between PEO and HEMC (also with ethylene oxide groups to dissociate Li-salt), as well as excess protonated branched groups in HEMC to attract more TFSI − anions. This organic filler also promotes the amorphization of the PEO structure and the mechanical strengthening of the polymer skeleton, characterized by Young's modulus of 46.95 MPa and tensile strength of 3.26 MPa. The porous texture in the polymer enables good anode-electrolyte interface compatibility due to the facile compaction at the 3D contact interface, which is favorable for the achievement of ultrastable Li plating/stripping cycling for at least 1000 cycles with an overpotential as small as 75 mV. The anode dendrite suppression endows Li|PEO16 –LiTFSI–20HEMC|LiFePO4 all-solid-state cells with long-term cycling (∼120 mA h g −1 at 1C for at least 300 cycles) and high-rate performance (80 mA h g −1 up to 2C). The widened electrochemical stability window (up to 5.56 V) is expected to improve the reversibility of higher voltage cathodes.